The effects of pre-op trainning on the anxiety levels of children in Corum/Turkey - Akca,Selen Ozakar (2015)
Summary Objective: all individuals regardless of their age or level of development require physical, emotional and cognitive preparation before an operation. It is known that the attitudes of pediatric nurses towards pediatric patients are influential on the anxiety levels of children awaiting an operation. This study aims to determine the effect of pre-op trainning on the anxiety levels of pediatric patients hospitalized for hernioplasty surgery. Methods: this cross sectional and quasi-experimental study included a total of 100 patients aged 7-12 years admitted for inguinal hernia surgery, 50 of which were the control group and 50 the experiment group. The data was gathered using the patients’ identification forms and a child steady state anxiety scale. Research data was evaluated with appropriate statistical methods. Results: the groups showed similar socio-demographic features and no statistically significant difference was observed (p>0.05). During the pre-op period neither of the groups showed any statistically significant difference in terms of both state and trait anxiety levels (p>0.05), however the experiment group showed a statistically significant drop in their anxiety levels during the post-op period (p<0.05). Conclusion: the state anxiety levels of children receiving a planned pre-op trainning are lower compared to children who did not receive such trainning. Reducing the anxiety levels of sick children is possible through giving visual and tangible information appropriate with the age and developmental level of the sick child during the pre-op period.